Kościoły klasztorne norbertanek w średniowiecznej Polsce w świetle reform monastycznych XI i XII w. - Sokołowski, Norbert (Jagiellonian University, 2019)
Theme of this thesis are churches of premonstratensians in medieval Poland shown in light of monastical reforms in 11th and 12th century. The purpose of this thesis is to connect medieval churches of premonstratensians in Poland: in Strzelno and in Kraków-Zwierzyniec with churches, which were built under influence of „Hirsau reform“. Thesis consists of 5 chapters. In the first one author presents in shortened form the beginning of premonstratensians, the female’s branch of this order and history of premonstratensians‘ beginning in Poland. In the second chapter author presents the state of research about churches in Strzelno, their history and description. In the third chapter author presents analogous informations about Saint Salvator‘s church in Kraków-Zwierzyniec. In the fourth chapter author presents the state of research and the history of Saint Augustine and John the Baptist church in Kraków-Zwierzyniec. In the fifth chapter author analyses similarities and differences between churches in Strzelno and Kraków and churches, mainly on german territories, which were built under influence of „Hirsau reform“.
Keywords: 🇵🇱 poland (general)

Życiowe dokonania Cypriana – zakonnika i biskupa wrocławskiego w latach 1201–1207 - Jerzak, Norbert (Wrocławski Przegląd Teologiczny, 2019)
Keywords: 👤 cyprian of wrocław

Kilka uwag o historii klasztoru w Opolu-Czarnowasach - Sadowski, Piotr (Opolskie Studia Administracyjno-Prawne, 2019)
Keywords: czarnowąsy

Krzyż i chwała : błogosławiona Bronisława i Konwent Panien Norbertanek na Zwierzyńcu w Krakowie = The cross and glory : blessed Bronislava and Norbertine Canonesses Convent in Zwierzyniec, Cracow - Stefaniak, Piotr (Księgarnia św. Jacka, 2019)
Keywords: zwierzyniec; 👤 bronislava of kamień

Problem genezy formalnej prezbiterium w krakowskim kościele Norbertanek na Zwierzyńcu - Cierpisz, Szymon (Rocznik krakowski Towarzystwo Miłośników Historii i Zabytków Krakowa, 2018)
Keywords: zwierzyniec

Norbertanki płockie - Kuźniewska, Zofia H. (Rocznik Towarzystwa Naukowego Płockiego, 2018)
Keywords: płock

Spory cystersów sulejowskich i norbertanów witowskich w XIII i XIV w - Parol, Jakub (Nasza Przeszłość : studia z dziejów Kościoła i kultury katolickiej w Polsce, 2018)
Keywords: witów

Zabytkowe hafty norbertanek żukowskich. Stan badań po czterdziestu latach - Stanilewicz, Karolina (Folia Historica Cracoviensia, 2018)
Keywords: żukowo

Liber ordinarius klasztoru premonstratensów na Ołbinie. Przyczynek do dalszych badań nad rękopisem - Szukiel, Piotr (Od Benedyktynów i Premonstratensów do Salezjanów: dzieje kościoła i parafii Św. Michała Archanioła na wrocławskim Ołbinie : materiały konferencji naukowej z okazji 70-lecia obecności salezjanów na wrocławskim Ołbinie (Wrocław, 28-29 kwietnia 2017 r.), 2018)
Keywords: wrocław

"Ducalis Parthenon Domûs Dei" : uwagi o architekturze i wymowie ideowej norbertańskiego kompleksu klasztornego w Czarnowąsach - Wojtyla, Arkadiusz (Sztuka dawnego Opola, 2018)
Keywords: czarnowąsy

Opowieść o „Domu Bożym”. Z dziejów zespołu klasztornego i kościoła pw. Bożego Ciała i św. Norberta w Czarnowąsach (1206/1228–2016) - Stefaniak, Piotr (2017)
Keywords: czarnowąsy

Znaczenie opactwa premonstrateńskiego w Brzesku-Hebdowie w strukturze zakonu i Kościoła w XIV–XV wieku - Podgórska-Mikuła, Arkadia (Studia z Dziejów Państwa i Prawa, 2016)
Th e importance of the Premonstratensian Abbey in Brzesko–Hebdów for the structure of the Order and the Church in the 14th and 15th centuries
Keywords: brzesko

Geneza i historia Rytu Premonstrateńskiego - Wendland, Mateusz (Liturgia Sacra, 2016)
The Premonstratensian, or Norbertine Rite is strictly related to the Order of Canons Regular, also known as the White Canons. Founded in the 12th century by Saint Norbert, the order at first adhered to liturgical practices that were common among the Canons Regular of Saint Augustine. The following article talks about the genesis and development of Norbertine liturgy, which survived the changes in practices made by the Council of Trent, but was eventually made obsolete by the Second Vatican Council.
Keywords: 🛐 liturgy

Kult świętych w średniowiecznym Nowym Sączy - Kazienko, Ewelina (Nasza Przeszłość. Studia z dziejów Kościoła i kultury katolickiej w Polsce, 2015)
Keywords: nowy sącz

Życie norbertanek żukowskich w wieku XV i na początku XVI stulecia - Możejko, Beata (Res Gestae, 2015)
Keywords: żukowo

Belbuc, Belboch, Bialoboki. Wprowadzenie do badan klasztoru prem onstratensów - Rębkowski, Marian (Klasztor premonstratensów w Bialobokach. Archeologia i historia, 2015)
Keywords: białoboki

Klasztor premonstratensów w Białobokach: archeologia i historia - Rębkowski, Marian; Biermann, Felix (Instytut Archeologii i Etnologii Polskiej Akademii Nauk : Ośrodek Archeologii Średniowiecza Krajów Nadbałtyckich, 2015)
Das Prämonstratenserstift in Belbuck : Archäologie und Geschichte
Keywords: białoboki

Inwentarz dóbr konwentu zwierzynieckiego w roku Pańskim 1722 spisany - Kazusek, Szymon (Nasza Przeszłość, 2013)
The subject of this publication is the only remaining early-modern inventory of the estates of the convent of Premonstratensians at Zwierzyniec near Cracow. This manuscript contains the description of the real estates in twenty villages being in the property of the Zwierzyniec convention in 1722. The inventory is an excellent source for the research on the farm economy in convent estate. The names of convent villages which the described real estates come from have in huge majority endured until contemporary times. At present some places are within the administrative borders of Cracow, Krzeszowice or Będzin, other exist under previous or modified names, whereas one of the described villages (Zakościele) has not remained until present times. Analysing the content of the inventory it is possible to obtain detailed information about the size, the state and the organisation of the buildings that were convent property, as well as about the leases and their financial aspects. The image emerging after studying the inventory shows a wide diversity of technical condition of farm buildings. What is more, the presented description includes information about buildings in very bad state as well as about renovated or new ones.
Keywords: zwierzyniec

Rola przedstawień drzewa genealogicznego zakonu w środowisku premonstratensów - Kwiatkowska-Frejlich, Lidia (Archiwa, Biblioteki I Muzea Kościelne, 2013)
The commonly known representation of Tree of Jesse, as inspired by the words „And the wand will come out of the root of Jesse and a flower will grow out of from its root” (Isaiah 11:1), proves the interpersonal relationships with Jesus and His messianic prophecy - by indicating on David. But since the earliest times this theme has been explored in the secular art because branching limbs with characters of descendants, growing from the parents’ chest, clearly illustrate the relations resulting from successions of generations within the family framework. This kind of representations was also popular in orders. At that time they not only provided the information on the background of spiritual path but also the assurance of its effectiveness on the way to reach Heaven. The images of the Order of Canons Regular of Prémontré, also known as the Premonstratensians, elaborated upon in this paper, was to make canons regular believe that abiding by the rules and laws made by the Order and praising the Eucharist, canons regular may master themselves to perfection and the saints of the order, who had already successfully fulfilled this recommendation, were the best teachers on the path of spiritual progress.
Keywords: 📚 premonstratensian (general)

O dawnych zwyczajach prawnych w swietle materialów procesovvych klasztoru sw. Wincentego na Oibinic we Wroclawiu z XIV wieku - Mlynarska-Kaletynowa, Marta (Z badan nad kultura spoleczenstw pradziejowych i wczesnosredniowiecznych: ksiega jubileuszowa dedykowana profesorowi Boguslawowi Gedidze, w osiemdziesiata rocznice urodzin przez przyjaciól, kolegów i uczniów, 2013)
Keywords: wrocław

Fundacja Opactwa Premonstratensów w Brzesku-Hebdowie - Podgórska, Arkadia (Meandry Historii: Starożytność – średniowiecze – nowożytność. Referaty wygłoSzone na XX ogólnopolskim zjeździe Historyków Studentów w Katowicach, 2013)
Keywords: brzesko

Klasztor Norbertanek w Imbramowicach. Studia i materiały - Dębowska, Maria (Biblioteka Ośrodka Archiwów Bibliotek i Muzeów Kościelnych Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2012)
Keywords: imbramowice

Kamienne plyty z ostatniej cwierci XII wieku w dawnym kosciele Norbertanek pw. Swietej Trójcy w Strzelnie - Szczęsna, Joanna (Ars omnia vincit. Studia z dziejów sztuki i kultury artystycznej, 2012)
Keywords: strzelno

Archiwum Norbertanek w Imbramowicach - Dębowska, Maria (Archiwa, Biblioteki i Muzea Kościelne, 2010)
Keywords: imbramowice

Wybrane problemy badawcze zwiazane z romanskim portalem z kosciola sw. Wincentego na Olbinie, obecnie w kosciele sww. Marii Magdaleny we Wroclawiu. Przeglad literatury - Fafara, Aldona (Sródmiejska katedra. Kosciól sw. Marii Magdaleny w dziejach i kulturze Wroclawia, 2010)
Keywords: wrocław

Uposażenie ziemskie klasztoru Norbertanek fundacji rybnickiej i czarnowąskiej do 1228 roku - Kopka, Monika (Sanctimoniales: Zakony żeńskie w Polsce i Europie Środkowej (do przełom XVIII i XIX wieku), 2010)
Landbesitz des Prämonstratenserinnenklosters der Stiftung von Rybnik und Czarnowąsy (Czarnowanz) bis 1228
Keywords: czarnowąsy; rybnik

Dzieje klasztorów norbertańskich w Żukowie - Okroy, Franciszek Ksawery (Wydawnictwo "ROST", 2010)
Keywords: żukowo

Tradycja norbertanska w przedstawieniach Marii z Dzieciatkiem trzymajacym jablko - Szczesna, Joanna (Roczniki humanistyczne, 2010)
Keywords: 📚 premonstratensian (general)